Ekstraksi Pemisahan Neodimium dari Samarium, Itrium dan Praseodimium Memakai Tri Butil Fosfat - Purwani, Maria Veronica; Suyanti, Suyanti (EKSPLORIUM, 2017)
The extraction of Nd(OH)3 (neodymium hydroxide) concentrate containing Y (yttrium), Sm (samarium) and Pr (praseodymium) as product of monazite processed has been done. The purpose of this study is to determine the separation of Nd from Y, Pr and Nd Sm in Nd concentrate. The aqueous phase was concentrated Nd (OH)3 in HNO3 and extractant while organic phase was Tri Butyl Phosphate (TBP) in kerosene. Parameters studied were pH and concentration feed, concentration of TBP in kerosene, extraction time and stirring speed. The result showed that the optimization of separation extraction neodymium from samarium, yttrium and praseodymium in Nd(OH)3 concentrated with TBP, obtained the optimum condition of pH = 0.2, concentration of feed 100 g /L, concentration of TBP in kerosene 5%, extraction time 15 minutes and stirring speed 150 rpm. With the conditions, Separation Factor (SF) obtained for Nd-Y, Nd-Pr, Nd-Sm are 2.242, 4.811, 4.002 respectively, while D and extraction efficiency of Nd are 0.236 and 19.07%.